DESIGN OF MOISTURE CONTENT TEST TOOL ON DRIED CLOVES BASED ON MICROCONTROLLER - Kolondam, Gracella; Pinontoan, Benny; Suwuh, Christian; Ketaren, Eliasta (STMIK TIME, 2025)
Determination of moisture content in dried cloves is an important step in the processing and storage process to ensure product quality and durability. This study aims to design and develop a microcontroller-based test tool for moisture content in dried cloves. This tool is designed using a DHT22 sensor connected to a microcontroller NodeMCU ESP8266 to measure moisture content in real-time and accurately. The data obtained from the sensor is processed by the microcontroller and displayed on Blynk Apps. The test results show that this test tool has a high level of accuracy and can be used as an efficient and practical alternative in testing the moisture content of dried cloves. The use of this tool is expected to increase the effectiveness of the processing and storage of cloves and reduce losses due to inappropriate moisture content.